Task-oriented for upper limb rehabilitation in people with multiple sclerosis: A systematic review of randomized trials. - Alashram, Anas R. (Journal of Bodywork & Movement Therapies, 2024)
To assess the effects of task-oriented (TO) training on upper limb dysfunction (ULD) in individuals with multiple sclerosis (PwMS). PubMed, Scopus, EMBASE, REHABDATA, Web of Science, and PEDro were searched from inception to May 2024. Only randomized that used TO training for upper limb functions of PwMS were included. One author screened records, extracted data, and evaluated the quality of the selected studies using the Cochrane Collaboration tool, and the results were subsequently checked by another researcher. Five randomized trials met the eligibility criteria. A total of 116 PwMS, 62 % of whom were women, were included in this study. Four studies revealed "high" quality, and one exposed a "moderate" quality. The studies incorporated in the analysis indicated that TO training did not yield a superior effect on upper limb recovery in PwMS compared to other conventional treatments. TO training is a safe intervention in PwMS. The evidence for the impact of TO training on upper extremity function in PwMS was limited. Additional studies with long-term follow-ups are required to understand the effects of TO on ULD in PwMS. • TO training is safe and well tolerated by the PwMS. • The evidence for the effect of TO training on the upper limb function in PwMS was limited. • The optimal treatment protocol remains unclear.